“Films as a tool for teaching culture in the efl classroom” - Cumbajín Ananganó, Verónica Daniela (2022)
The present research report aims to identify the positive and negative perceptions derived from an action research experience of the use of films for teaching culture-based lessons in an online class in first-year high school students. To achieve this objective, an action research methodology was developed, in this sense, lesson plans were designed and implemented over seven weeks through an academic intervention of two groups of participants, the first group was of first year high school students belonging to the Educational Unit "Luis Fernando Ruiz” and the second group was of volunteer first year high school students from different public institutions in Quito. The data were obtained through some instruments applied, which included a teacher's reflection form, a peer observer´s table and a survey to students to obtain their comments. As a result, analysis of the data suggested the positive perceptions to teach culture with films in an online high school class, such as: a) Motivation; b) Cultural learning; c) Accessible online tools; d) Clear teacher’s instructions; e) Good didactic material. And the negative perceptions are: a) Time management; b) Technology problems; c) Student participation; d) Lack of understanding. However, there were some limitations, which were related to the number of classes taught to students, number of students who attended classes, and those students who completed the survey. From these results, it is concluded that the use of films in teaching English contributes to students´ cultural knowledge and reinforces language learning. By integrating all these tips in the teaching process, it is possible to teach culture to students in a motivating way, permitting to achieve the lesson objectives about improving cultural knowledge.